Plain Talk about Churches and Money - McNamara, Patrick; Zech, Charles; Dean Hoge (Rowman & Littlefield Publishers, 1998)
Based on extensive research, this volume offers insight and help on the key fiscal topics confronting church leaders today, including: Why is the church so uneasy with the topic of money? Is there a difference between stewardship and fundraising? How can we motivate giving? Should we invest church funds? It tackles the resistance, fears, and difficulties about money common in congregations. The book is must reading for lay leaders and anyone in pastoral ministry today.